The problem is: I have a continuous $f: \mathbb R_+ \to \mathbb R$ which satisfies $f(xy)=xf(y)+yf(x)$ for all $x,y \in \mathbb R_+$. I want to prove that $f$ is differentiable.

The problem is equivalent to proving that $f'(1)$ exist. I have no idea how to go on.


Divide the functional equation by $xy$ to get


Set $g(x)=\frac{f(x)}x$ so that


This is actually well known, and if $g(x)$ is continuous, then the solution is given by


which implies


  • 1
    $\begingroup$ A list of common functional equations may be found here for reference. ;-) $\endgroup$ – Simply Beautiful Art Jan 10 '17 at 2:27
  • $\begingroup$ How do you know that a continuous $g:\mathbb{R} ^{+} \to \mathbb{R} $ satisfying $g(xy) =g(x) +g(y) $ is of the form $g(x) = a\log x$? The main issue in establishing this is to prove the existence of derivative $g'$ and it appears difficult unless we use integrals like in my answer. $\endgroup$ – Paramanand Singh Jan 10 '17 at 4:53

Using integrals the job is easy. Since $f$ is continuous the anti-derivarive of $f$, say $F$ exists. Now integrate the functional equation with respect to $y$ on interval $[1,2]$ to get $$\frac{F(2x)-F(x)}{x}=x(F(2)-F(1))+ \frac{3}{2}f(x)$$ Since $F'$ exists it now follows that $f'(x) $ exists for all $x\in(0,\infty)$.

The problem is difficult if we stick to differential calculus only. I have managed to make some progress to solve the problem using methods of differential calculus and I present the same below.

Dividing by $xy$ we get the functional equation $$\frac{f(xy)}{xy} = \frac{f(x)}{x} + \frac{f(y)}{y}\tag{1}$$ and if we put $g(x) = f(x)/x$ then $$g(xy) = g(x) + g(y)\tag{2}$$ We prove the following theorem:

Theorem: If $g:\mathbb{R}^{+}\to\mathbb{R}$ is continuous at a point $c \in \mathbb{R}^{+}$ and satisfies $g(xy) = g(x) + g(y)$ for all $x, y \in \mathbb{R}^{+}$ then $g(x)$ is differentiable for all $x \in \mathbb{R}^{+}$ and $g'(x) = g'(1)/x$.

First we prove that $g$ is continuous on $\mathbb{R}^{+}$. Let $x > 0$ and $x \neq c$. Then we have $$\lim_{h \to 0}g(x + h) = \lim_{h \to 0}g(x/c)+g (c + ch/x) = g(x/c)+g(c) = g(x)$$ From the functional equation the following properties are obvious $$g(1) = 0, g(1/x) = -g(x), g(x/y) = g(x) - g(y), g(x^{q}) = qg(x), q\in \mathbb{Q}\tag{3}$$ Next we prove that $x = 1$ is the only solution for $g(x) = 0$. More precisely we prove that

If a continuous function $g:\mathbb{R}^{+}\to\mathbb{R}$ satisfies functional equation $(2)$ and there is a number $k \neq 1$ such that $g(k) = 0$ then $g(x) = 0$ for all $x\in\mathbb{R}^{+}$.

Let us suppose that $k \neq 1$ and $g(k) = 0$ and then by $(3)$ we have $g(k^{q}) = 0$ for all $q \in \mathbb{Q}$. Now it can be proved with some effort that every positive real number is an accumulation point of set $A = \{k^{q}: q\in \mathbb{Q}\}$ or in other words if we take any positive real number $x$ then every neighborhood of $x$ contains points of the form $k^{q}$. It now follows by sign preserving nature of continuous functions that $g(x) = 0$ for all positive $x$.

So one solution of the functional equation is the constant $0$ function and apart from this trivial solution any other $g$ is such that $g(x) = 0\Rightarrow x = 1$. From the relation $g(x/y) = g(x) - g(y)$ it then follows that $g$ is one-one function. We further note that any continuous one one function is strictly monotone (this is an easy consequence of intermediate value property of continuous functions) and hence $g$ is strictly monotone.

It follows that if $k \neq 1$ then $g(k)\neq 0$ and $g(k^{n}) = ng(k)$ for all integers $n$ so that function $g$ can take arbitrarily large negative and positive values. By intermediate value property it follows that range of $g$ is $\mathbb{R}$ and hence $g$ is one-one onto function.

Next we prove that if $g'(1)$ exists then $g'(x) = g'(1)/x$. Clearly we have \begin{align} g'(x) &= \lim_{h \to 0}\frac{g(x + h) - g(x)}{h}\notag\\ &= \lim_{h \to 0}\frac{g(1 + h/x)}{h}\notag\\ &= \lim_{h \to 0}\frac{g(1 + h/x) - g(1)}{h/x}\cdot\frac{1}{x}\notag\\ &= \frac{g'(1)}{x}\notag \end{align} We next need to show that $g'(1)$ exists or more explicitly the following limit exists $$\lim_{x \to 1}\frac{g(x)}{x - 1} = g'(1)\tag{4}$$ I have not been able to prove the existence of this limit in a direct manner. Rather I use the fact that $g$ is invertible and thus there is a function $h:\mathbb{R}\to\mathbb{R}^{+}$ such that $g(h(x)) = x, x\in \mathbb{R}$ and $h(g(x)) = x, x \in \mathbb{R}^{+}$. Moreover because of equation $(2)$ the function $h$ satisfies the functional equation $$h(x+y) = h(x)h(y)\tag{5}$$ and it has already been established that under these conditions the limit $$\lim_{x \to 0}\frac{h(x) - 1}{x}\tag{6}$$ exists and is non-zero unless $h$ is constant. Putting $h(x) - 1 = t$ we see that $x = g(1 + t)$ and as $x \to 0, t \to 0$ and thus $$\lim_{t \to 0}\frac{g(1 + t)}{t}$$ exists and thus the limit $g'(1)$ in equation $(4)$ exists.

It is now clear that $f(x) = xg(x)$ is differentiable for all $x > 0$.

In the above we have only discussed that if a function $g$ satisfies the equation $(2)$ and is continuous then it is differentiable also. With slightly more effort we can show that such functions actually exist. One way is to integrate the equation $g'(x) = g'(1)/x$ to get $$g(x) = g'(1)\int_{1}^{x}\frac{dt}{t}\tag{7}$$ so that any multiple of the above integral is a solution for $(2)$. There is another way to find an expression for $g$. Let $x\neq 1$ and then we know that $x^{1/n}\neq 1$ for all positive integers $n$ and also $x^{1/n}\to 1$ as $n\to\infty $. We then have $$g(x) =ng(x^{1/n})=n(x^{1/n}-1)\cdot\frac{g(x^{1/n})}{x^{1/n}-1}$$ Taking limits as $n\to\infty$ and noting that fraction on right in above equation tends to $g'(1)$ we can see that $$g(x) = g'(1)\lim_{n\to\infty}n(x^{1/n}-1)\tag{8}$$ Thus the solution $g$ is always a constant multiple of the limit in above equation. Both the integral in $(7)$ and the limit in $(8)$ are equivalent expressions for the logarithm function conventionally denoted by $\log x$ and the theory of this function can be developed independently using either the integral or the limit approach. The current answer shows that using functional equation $(2)$ and assumption of continuity we can discover a very useful and important function called logarithm.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.